2022
DOI: 10.1007/s00122-022-04219-4
|View full text |Cite
|
Sign up to set email alerts
|

Separation of the effects of two reduced height (Rht) genes and genomic background to select for less Fusarium head blight of short-strawed winter wheat (Triticum aestivum L.) varieties

Abstract: Key message FHB resistance shared pleiotropic loci with plant height and anther retention. Genomic prediction allows to select for genomic background reducing FHB susceptibility in the presence of the dwarfing allele Rht-D1b. Abstract With the high interest for semi-dwarf cultivars in wheat, finding locally adapted resistance sources against Fusarium head blight (FHB) and FHB-neutral reduced height (Rht) genes is of utmost relevance. In this study, 401 ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 104 publications
2
7
0
Order By: Relevance
“…The highest prediction ability was found for GBLUP + AnthesisDate + Rht‐D1 (PA = 0.87 ± 0.03), followed by GBLUP + AntherRetention + Rht‐D1 (PA = 0.84 ± 0.04) in a fivefold cross‐validated procedure. This again highlights the importance of integration of morphological traits for FHB resistance that was also reported elsewhere (Akohoue et al, 2022; Buerstmayr & Buerstmayr, 2016; Lu et al, 2013).…”
Section: How To Proceed In Future Resistance Breedingsupporting
confidence: 83%
See 1 more Smart Citation
“…The highest prediction ability was found for GBLUP + AnthesisDate + Rht‐D1 (PA = 0.87 ± 0.03), followed by GBLUP + AntherRetention + Rht‐D1 (PA = 0.84 ± 0.04) in a fivefold cross‐validated procedure. This again highlights the importance of integration of morphological traits for FHB resistance that was also reported elsewhere (Akohoue et al, 2022; Buerstmayr & Buerstmayr, 2016; Lu et al, 2013).…”
Section: How To Proceed In Future Resistance Breedingsupporting
confidence: 83%
“…Moreover, in the meantime, we know that Rht‐B1b and Rht‐D1b both increase anther retention (Buerstmayr & Buerstmayr, 2016) that might be an important part of the dwarfing gene's enhancement of FHB susceptibility. A recent path analysis within the European winter wheat diversity panel showed that the morphological factors plant height and anther retention have a narrow genotypic correlation with FHB severity ( r g = −.64 and .74, respectively) and explain together 67% of the phenotypic variation for FHB severity (Akohoue et al, 2022). A 1% higher anther retention caused a 0.57% higher FHB severity.…”
Section: Breeding Progress and Challenges For Selection Of Fhb Resist...mentioning
confidence: 99%
“…These authors also suggested that, while Rht ‐ D1a could be used as elite pollinators, the semi‐dwarf Rht2 could be fixed in the female pool, and due to the semi‐dominant inheritance of this allele, the resulting hybrids would possess the desired plant height reduction (Boeven et al., 2016; Börner et al., 1996; Zhao et al., 2014). The exploration of modern Green Revolution Rht genes such as Rht24b has shown the potentiality of decreasing plant height without penalties in grain yield (Tian et al., 2022) while increasing anther extrusion and resistance against Fusarium head blight compared to the Green Revolution semi‐dwarf allele Rht2 (Akohoue et al., 2022; Miedaner et al., 2022; Würschum et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…and Rht-D1, and not as a general relationship between the two phenotypes (Akohoue et al, 2022;Srinivasachary et al, 2008;Voss et al, 2008). Both homeologous copies of Rht1 encode DELLA proteins that, beyond their role in directly regulating the gibberellic acid response, additionally interact with signalling pathways implicated in plant response to biotic stress (Navarro et al, 2008).…”
Section: Purging Of Fhb Susceptibility (S) Genes and Removing Linkage...mentioning
confidence: 99%
“…A decrease in mature plant height may bring wheat heads closer to the soil surface and increase exposure of plants to rain‐splashed pathogens. Recent work however has suggested a link between plant height reduction and increased FHB susceptibility primarily as a result of using green revolution genes Rht‐B1 and Rht‐D1 , and not as a general relationship between the two phenotypes (Akohoue et al, 2022; Srinivasachary et al, 2008; Voss et al, 2008). Both homeologous copies of Rht1 encode DELLA proteins that, beyond their role in directly regulating the gibberellic acid response, additionally interact with signalling pathways implicated in plant response to biotic stress (Navarro et al, 2008).…”
Section: Purging Of Fhb Susceptibility (S) Genes and Removing Linkage...mentioning
confidence: 99%